2023
DOI: 10.3389/fcosc.2023.1126168
|View full text |Cite
|
Sign up to set email alerts
|

“Development” definitions of internally displaced people and the government: A study of the Chenchu tribe in the Nallamala forest of southern India

Abstract: The Government of India’s twin objectives of protecting the tiger population in the Nallamala forest and providing “development” to the indigenous Chenchu people have resulted in an ongoing process of displacement of the Chenchu people from the forest to the town fringes. While the conservation-displacement nexus has bridged new anthropocentric pathways for development, it has also created deeper crevices in the innate relationships of the Chenchu with the forests and tigers. The research uses a bottom-up appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 50 publications
(59 reference statements)
0
1
0
Order By: Relevance
“…For example, Stoffle found that by respecting the sovereignty of the Skokomish Indian people and involving the tribes in watershed management, tribal cultures could be fully utilised in restoring channel-maintaining flows and salmon populations (Stoffle, 2022). Jinka et al found that indigenous people, government representatives, and local nongovernmental organisations had different perceptions of tiger conservation and economic development (Jinka and Hoffman, 2023). The key to achieving balanced development of nature reserves is promoting cooperation and communication between all parties.…”
Section: Income Stratificationmentioning
confidence: 99%
“…For example, Stoffle found that by respecting the sovereignty of the Skokomish Indian people and involving the tribes in watershed management, tribal cultures could be fully utilised in restoring channel-maintaining flows and salmon populations (Stoffle, 2022). Jinka et al found that indigenous people, government representatives, and local nongovernmental organisations had different perceptions of tiger conservation and economic development (Jinka and Hoffman, 2023). The key to achieving balanced development of nature reserves is promoting cooperation and communication between all parties.…”
Section: Income Stratificationmentioning
confidence: 99%